(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The content of this letter is mainly to draw the attention of the scientific community to the space problem, and to pray for scientists such as mathematics, physics and system science to prove the existence in space and space. With all due respect, the scientific development in the past 500 years has been developed on the basis of no knowing what is the real space and the existence in space. 2500 years ago, the ancient Greek philosophers, the eastern Taoist philosophy and the Buddhist philosophy, under the continuous inheritance of their respective ideas, once expressed and answered this question to later generations. The ancient Greek philosophers’ expression of space and existence in space was not systematic, and the expression was materialistic, and the problem of cosmic origin and the problem of existence in space were put aside by Aristotle. The great Aristotle, after seriously thinking about the problem of space in 《Physics》, put the problem of space and the existence in space in 《Metaphysics》 with reverence, and put it in the human mind. Philosophy, therefore, became a philosophy of science. After Aristotle put aside the problem of space and the existence in space, religion put this problem in human beliefs.